2020
DOI: 10.1177/1078390320915257
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Autism Symptoms After Comprehensive Intensive Early Interventions in Community Settings

Abstract: BACKGROUND: Preschool children with autism in southern Sweden participated in a comprehensive Naturalistic Developmental Behavioral Intervention (NDBI) program. AIMS: To evaluate the ongoing NDBI program by comparing the pre- and postintervention outcomes in terms of improved autism symptom severity. METHOD: The improvement of Autism Diagnostic Observation Schedule (ADOS-R) test results between baseline and evaluation among children participating in the NDBI program ( n = 67) was compared with the results amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…As such, norm-referenced standardized scores are less relevant in school-based programs than is progress on individualized goals. In contrast, some comprehensive autism programs have explicitly focused on changing the core features of autism (Haglund et al 2020 ), noting that IEP goals are not always aligned with these core features (Anderson et al 2020 ). In such cases, changes in diagnostic (e.g., ADOS) and standardized norm-referenced measures (e.g., SRS, SCQ) could be considered the primary outcome variables of interest.…”
Section: Discussionmentioning
confidence: 99%
“…As such, norm-referenced standardized scores are less relevant in school-based programs than is progress on individualized goals. In contrast, some comprehensive autism programs have explicitly focused on changing the core features of autism (Haglund et al 2020 ), noting that IEP goals are not always aligned with these core features (Anderson et al 2020 ). In such cases, changes in diagnostic (e.g., ADOS) and standardized norm-referenced measures (e.g., SRS, SCQ) could be considered the primary outcome variables of interest.…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent screening was based on the titles and abstracts of the remaining articles, with the exclusion of reviews and non-relevant articles such as studies with no comparison or control group or qualitative-only designs. The inclusion criteria for the review were as follows: (1) randomized controlled trials (RCTs) or pre-post studies involving children with autism or ASD; (2) study participants in the study samples had to be under 18 years of age; (3) studies were included if they were reported on EFA outcomes; (4) if studies were interventions; and (5) articles had to be published in English.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the growing prevalence of ASDs, effective treatments for the disorder are limited. Traditional therapies, such as behavioral interventions and medications, have shown some efficacy, but they often have significant limitations and may not be suitable for all individuals with ASDs ( 2 ). Therefore, there is a need for novel treatment approaches that can effectively address the core symptoms of ASDs.…”
Section: Introductionmentioning
confidence: 99%
“…That study caused a paradigm shift regarding treatment efficacy due to the significant improvements and even “recovery” for almost half of the children with ASD after receiving excellent treatment with early intervention at a sufficient intensity. Models based on ABA originating from the Lovaas method are collectively referred to as early intensive behavioral intervention (EIBI) ( 9 ), which involves manual-based intensive programs and targets a comprehensive series of skills for training, practice, and generalization ( 10 ). Improvements afforded by EIBI, which is recognized as a preferred intervention for children with ASD, have been demonstrated in the areas of adaptive behavior, IQ, communication, socialization, and daily living skills ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%